Flagrante delicto and human rights. Rethinking the criminal law of the citizen - Figueroa Gutarra, Edwin (2022)
The increasing demand on the State to fight against crime has led strongly to consider that there is a criminal law of the enemy, as stated by Günther Jakobs, which is expressed in harsher punishments, longer prison terms, among other ideas. In this regard, the trial through Units against Flagrante Delicto, as Peru has been implementing, represents a better coincidence with the criminal law of the citizen, as proposed by said author, to understand a better consolidation of human rights. Let us prosecute the crime, it is necessary, but let us do so within the framework of respect for the principle of dignity of the person.